2011
DOI: 10.1007/s00010-011-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Metric trees of generalized roundness one

Abstract: Abstract. Every finite metric tree has generalized roundness strictly greater than one. On the other hand, some countable metric trees have generalized roundness precisely one. The purpose of this paper is to identify some large classes of countable metric trees that have generalized roundness precisely one.At the outset we consider spherically symmetric trees endowed with the usual path metric (SSTs). Using a simple geometric argument we show how to determine reasonable upper bounds on the generalized roundne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…If f (k) = 1 for all k ≥ 0, the resulting metric trees C( f ) and C m ( f ) will be denoted by C(1) and C m (1), respectively. In other words, C(1) and C m (1) are the combs C and C m endowed with the usual combinatorial path metric δ. Caffarelli et al [2] have shown that ℘ C m (1) → 1 as m → ∞. Hence, ℘ C(1) = 1.…”
Section: Comb-like Graphs Of Generalised Roundness Onementioning
confidence: 94%
See 4 more Smart Citations
“…If f (k) = 1 for all k ≥ 0, the resulting metric trees C( f ) and C m ( f ) will be denoted by C(1) and C m (1), respectively. In other words, C(1) and C m (1) are the combs C and C m endowed with the usual combinatorial path metric δ. Caffarelli et al [2] have shown that ℘ C m (1) → 1 as m → ∞. Hence, ℘ C(1) = 1.…”
Section: Comb-like Graphs Of Generalised Roundness Onementioning
confidence: 94%
“…We proceed to show that large classes of divergent and convergent SSTs have generalised roundness one. The following lemma is a variation of [2,Theorem 2.1]. As the statement of the lemma is complicated, we will comment on the intuition behind this result.…”
Section: Convergent and Divergent Spherically Symmetric Trees Of Genementioning
confidence: 98%
See 3 more Smart Citations